Hubungan antara gaya pembelajaran pelajar cemerlang dan pelajar lemah dengan pencapaian Matematik di kalangan pelajar tingkatan empat - Ng, Yau Hing @ Donny (2010)
The study looked at the relation of learning style of excellent students and weak students with the mathematics achievement. The study also looked at the differences of learning styles in term of gender and differences of learning styles with mathematics achievement. 140 Form Four students from school A in Beluran district were chosen as respondents in the study. The instrument for learning style was taken and modified from Grasha-Riechmann (1996) questionnaire. The questionnaire was used to determine the average level of learning styles components. The data were gathered and analyzed using Pearson correlation and t-test. The findings showed that there was no relation of independent learning style, collaborative learning style, dependent learning style, competitive learning style, participant learning style and avoidant learning style. Correlation analysis also showed that there was a relation between excellent students and weak students with the mathematics achievement. Ttest analysis showed the difference between male and female students in dependent learning style and participant learning style with the mathematics achievement. There was no different amongst excellent students and weak students with the form four mathematics achievement